Pemanfaatan Kunyit Putih (Curcuma Alba) Sebagai Tanaman Obat Keluarga Di Desa Kelambir V Kebun - Zamriyetti Zamriyetti; Refnizuida Refnizuida; Maimunah Siregar; Akhamad Rifai Lubis (Smart Education, 2021)
Abstract: Plants are a storehouse that has a million benefits including medicine for various diseases. Communities must have an awareness that grows along with the development of knowledge about their natural environment. Family Medicinal Plants (TOGA) are basically plants planted in the yard, garden or plot of land that are used as a place for cultivating medicinal plants in order to meet the family's need for medicines. Knowledge about the use of home yards by cultivating various medicinal plants is expected to increase public knowledge about the usefulness and efficacy of several medicinal plants that can be developed in the residential environment and can also be used to increase family income, at least it can be used to maintain family health. To be able to realize these expectations, community service activities are carried out in the form of: 1. Lectures and discussions. 2. Demonstration of making a health drink made from white turmeric. With this activity, it is hoped that the goals to be achieved at the end of the program, namely: